Fractions, Contamination and Health Risk of Cadmium in Alpine Soils on the Gongga Mountain, Eastern Tibetan Plateau - Wang, Zhiguo; Bing, Haijian; Zhu, He; Wu, Yanhong (Bulletin of environmental contamination and toxicology, 2021)
Anthropogenic cadmium (Cd) in alpine soils is mainly from long-range atmospheric transport. Because of the high toxicity and mobility, whether the accumulation of Cd in the soils threats to ecosystem safety remains unclear. The fractions of soil Cd along three altitudinal transects on Gongga Mountain were analyzed to decipher the drivers on its mobility, and its contamination and health risk were assessed. The concentrations of Cd in the organic (O) and mineral (A) horizons were significantly higher on the eastern and southern transects than the western transect. The Cd fractions in the two horizons dominated by acid-soluble and reducible Cd. Soil organic matter and pH modulated the mobilization of soil Cd. Cadmium reached a moderate contamination level on the eastern and southern transects, but no or slight contamination on the western transect. The soil Cd had a low non-carcinogenic risk and no carcinogenic risk despite of adults or children.